Analisis Jumlah Sel Monosit yang Mengekspresikan Tnf-Α setelah dipapar Porphyromonas Gingivalis dan Tulang Ikan Kuniran (Upeneus Sulphureus) dengan Teknik Imunositokimia - Fiona Budi Amarta Domini; I Dewa Ayu Ratna Dewanti; Erawati Wulandari (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
Monocytes play a role in the first defense against microorganisms that harm the body by activating nuclear factor kβ (Nf-kβ) which is the main regulator of inflammatory genes, one of which is TNF-α. TNF-α at excessive levels will cause tissue damage. Therefore an immunomodulator is needed which can regulate the body's immune system. One natural ingredient that acts as an immunomodulator is fish bones. Purpose of research: To analyze the effect of goatfish’s bone extract on TNF-α expression in human monocytes exposed to P. gingivalis. Method: experimental laboratories in vitro. TNF-α expression was tested by imunocytochemical techniques. Results: The results showed that the average number of monocytes expressing TNF-α in group P1 (group of diclofenac sodium) was 42.33 cells per cell. In the P2 group (P. gingivalis group) was 95 cell percent cells and for P3 (fish bone group) was 74.33 cells per cell and the control group was 11.66 cells per hundred cells. Conclusion: goatfish’s bone extract can act as an anti-inflammatory which is effective in reducing TNF-α expression in monocyte exposed to P. gingivalis but less effective than diclofenac sodium.